2016
DOI: 10.1186/s12882-016-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Ergocalciferol treatment does Not improve erythropoietin utilization and hospitalization rate in hemodialysis patients

Abstract: Background: Vitamin D (25-hydroxyvitamin D; 25[OH]D) deficiency (VDD) is highly prevalent in chronic kidney disease. The aim of this study was to evaluate the effect of oral ergocalciferol supplementation on requirement of erythropoietin (EPO) and active vitamin D analogues, and hospitalization rate in maintenance hemodialysis (HD) patients.Methods: This retrospective cohort study included 186 patients who were on HD for 3 months and had 25(OH)D levels < 30 ng/ml. Over 1-year period, 107 patients were suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Vitamin D supplementation culminated in a significant decrease in PTH levels, as reported in Nand and Mittal (2017) and Matias et al (2010), in Kumar et al (2011), Porter et al (2013, Miskulin et al (2016), Agarwal et al (2016) and Obi et al (2020) no significant difference was found in PTH levels.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Vitamin D supplementation culminated in a significant decrease in PTH levels, as reported in Nand and Mittal (2017) and Matias et al (2010), in Kumar et al (2011), Porter et al (2013, Miskulin et al (2016), Agarwal et al (2016) and Obi et al (2020) no significant difference was found in PTH levels.…”
Section: Resultsmentioning
confidence: 55%
“…In turn, Nand and Mittal (2017) found a reduction in the dose of EPO and an increase in hemoglobin levels with cholecalciferol supplementation. Agarwal et al (2016), Miskulin et al (2016) and Obi et al (2020) found no significant difference between the groups regarding the dose of EPO, epoetin and darbepoetin, respectively.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…36 Vitamin D supplementation had no effect on ESA dose in vitamin D deficient haemodialysis patients. 37,38 The underlying mechanism among CKD-MBD, anaemia and ESA hyporesponsiveness is not well understood. Since FGF23 is associated with both CKD-MBD and anaemia, FGF23 may be the factor which connects them.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, treatment with active vitamin D in haemodialysis patients with secondary hyperparathyroidism increased FGF23 levels 36 . Vitamin D supplementation had no effect on ESA dose in vitamin D deficient haemodialysis patients 37,38 . The underlying mechanism among CKD‐MBD, anaemia and ESA hyporesponsiveness is not well understood.…”
Section: Discussionmentioning
confidence: 99%